Comparative analysis of cystic biliary atresia and choledochal cysts - Chen, Yu-tong; Gao, Ming-juan; Zheng, Ze-bing; Huang, Lu; Du, Qing; Zhu, Dai-wei; Liu, Yuan-mei; Jin, Zhu (Frontiers in Pediatrics, 2022)
Objective Cystic biliary atresia (CBA) is a rare and peculiar type of biliary atresia (BA) that is easily confused with infantile choledochal cysts (CCs). This study explored information for early CBA diagnosis and treatment. Method The authors retrospectively analyzed the clinical data of 32 children with hilar cysts from January 2013 to May 2021. According to the diagnosis, they were divided into the CBA (n = 12) and CC (n = 20) groups. Patient features, biochemical indexes, preoperative ultrasound characteristics, cholangiography features, and intraoperative findings were analyzed and compared between the two groups. Results The alanine aminotransferase, aspartate aminotransferase, total bilirubin, and direct bilirubin levels in the CBA group were higher than in the CCs group (P < 0.05). Additionally, B-mode ultrasound showed a cystic mass in front of the hepatic hilum, and the cyst size was much smaller in the CBA group compared with the CC group (2.2 ± 1.3 cm vs. 6.0 ± 2.2 cm, P < 0.001). Among all of the parameters, cyst width was the most accurate for identifying CBA and CCs. A cutoff value of 2.5 cm (area under the curve, 0.98, P < 0.001) showed 90.9% sensitivity and 95% specificity for cyst size. Conclusion For children with early-onset severe jaundice, and if the width of the cystic mass was ≤2.5 cm, a diagnosis of CBA was highly likely. Early cholangiography and surgical treatment are necessary for the effective treatment of these infants.